Selective localization of myosin‐I proteins in macropinosomes and actin waves. Issue 2 (22nd February 2016) - Brzeska, Hanna; Koech, Hilary; Pridham, Kevin J.; Korn, Edward D.; Titus, Margaret A.
Abstract : Class I myosins are widely expressed with roles in endocytosis and cell migration in a variety of cell types. Dictyostelium express multiple myosin Is, including three short‐tailed (Myo1A, Myo1E, Myo1F) and three long‐tailed (Myo1B, Myo1C, Myo1D). Here we report the molecular basis of the specific localizations of short‐tailed Myo1A, Myo1E, and Myo1F compared to our previously determined localization of long‐tailed Myo1B. Myo1A and Myo1B have common and unique localizations consistent with the various features of their tail region; specifically the BH sites in their tails are required for their association with the plasma membrane and heads are sufficient for relocalization to the front of polarized cells. Myo1A does not localize to actin waves and macropinocytic protrusions, in agreement with the absence of a tail region which is required for these localizations of Myo1B. However, in spite of the overall similarity of their domain structures, the cellular distributions of Myo1E and Myo1F are quite different from Myo1A. Myo1E and Myo1F, but not Myo1A, are associated with macropinocytic cups and actin waves. The localizations of Myo1E and Myo1F in macropinocytic structures and actin waves differ from the localization of Myo1B. Myo1B colocalizes with F‐actin in the actin waves and at the tips of mature macropinocytic cups whereas Myo1E and Myo1F are in the interior of actin waves and along the entire surface of macropinocytic cups. Our results point to different mechanisms of targeting of short‐ and long‐tailed myosin Is, and are consistent with these myosins having both shared and divergent cellular functions. © 2016 Wiley Periodicals, Inc.